Manajemen Pengelolaan Usaha Bimbingan Belajar di Bimbel Progress99 Krapyak Pekalongan - Salsabila Salsabila; Bintani Qurrota A'yun; Rif'an Rizki Hidayat; Ahmad Rizal Akbar (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to describe the implementation of management practices in the non-formal education institution Bimbingan Belajar (Bimbel) Progress99 located in Krapyak, Pekalongan. The focus of this research is on how the institution applies management functions such as planning, organizing, staffing, directing, and controlling in its operational activities. This research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation involving the manager, tutors, and students. The results show that Bimbel Juragan99 has applied management principles in a simple yet effective manner. The learning programs offered include private, semi-private, and regular classes, which are adjusted according to students’ needs and characteristics. Although the institution still faces limitations in facilities and uses a manual administrative system, it continues to grow due to adaptive promotional strategies and the entrepreneurial spirit of its manager. Thus, the consistent application of good management practices plays an essential role in ensuring sustainability and improving the quality of educational services in non-formal tutoring institutions.